A study on the use of technology in university based music education programs:: the current situation in China and emerging trends from ISME - Zhang, Peiy; Marins, Paulo Roberto Afonso (Música em Contexto, 2018)
This paper presents a discussion concerning the use of Information and Communication Technologies (ICTs) in university based music education degree programs and also in selected ICT based music courses. In this manuscript, the current situation in China is presented and compared to the emerging trends of research published at the 32nd World Conference of the International Society of Music Education (ISME). It is hoped that a number of possible topics for research and teaching practice innovation are going to be drawn and elicited from the discussions reported in this paper.